2015
DOI: 10.1002/anie.201411409
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Catalysis of Photochemical Reactions

Abstract: The nature of the excited state renders the development of chiral catalysts for enantioselective photochemical reactions a considerable challenge. The absorption of a 400 nm photon corresponds to an energy uptake of approximately 300 kJ mol(-1) . Given the large distance to the ground state, innovative concepts are required to open reaction pathways that selectively lead to a single enantiomer of the desired product. This Review outlines the two major concepts of homogenously catalyzed enantioselective process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
269
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 581 publications
(276 citation statements)
references
References 211 publications
0
269
0
7
Order By: Relevance
“…Recent research activities have demonstrated a vast number of structural design methods of small molecular 8,10,[16][17][18][19][20] or macromolecular [21][22][23][24][25][26][27][28][29][30] OS systems as efficient photocatalysts for visible light-promoted photoredox reactions. Nevertheless, most developed OS photocatalysts, similar to traditional transition metal complexes, [31][32][33][34][35][36][37][38] are single photocatalytic systems. As illustrated in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research activities have demonstrated a vast number of structural design methods of small molecular 8,10,[16][17][18][19][20] or macromolecular [21][22][23][24][25][26][27][28][29][30] OS systems as efficient photocatalysts for visible light-promoted photoredox reactions. Nevertheless, most developed OS photocatalysts, similar to traditional transition metal complexes, [31][32][33][34][35][36][37][38] are single photocatalytic systems. As illustrated in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…[41] We were particularly inspired by MacMillans seminal work on merging photoredox catalysis with asymmetric catalysis. [42] Specifically, in 2008, Nicewicz and MacMillan demonstrated that the enantioselective a-alkylation of aldehydes can be accomplished by employing a combination of a chiral secondary amine for enamine catalysis and a photoredox catalyst for photoinduced electron transfer. [43] We wondered whether our chiral bis-cyclometalated iridium Lewis acids could be uniquely suited to merge visible-light-induced photoredox chemistry and asymmetric catalysis with just a single catalyst.…”
Section: Dual Chiral Lewis Acid/photoredox Catalystsmentioning
confidence: 99%
“…[5,7,8] Aufd er Suche nach Substraten, die keine nennenswerte langwellige Absorption aufweisen, die aber nach Aktivierung mit einer Säure eine starke bathochrome Verschiebung zeigen, haben wir Enone getestet, deren Carbonylgruppe in ein 1,3-Dithian überführt wurde (Enondithiane). Das mutmaßlich durch Protonierung entstehende Thioniumion sollte im sichtbaren Bereich anregbar sein (l abs > 380 nm) [9] und damit eventuell eine Brønsted-Säure-katalysierte [2+ +2]-Photocycloaddition eingehen.…”
Section: Von Allen Photochemischen Reaktionen Kommt Der [2+ +2]-unclassified